Asymptomatic Leishmania infantum infection in blood donors living in an endemic area, northeastern Italy. Issue 1 (January 2020) - Ortalli, Margherita; De Pascali, Alessandra Mistral; Longo, Serena; Pascarelli, Nadia; Porcellini, Andrea; Ruggeri, Deborah; Randi, Vanda; Procopio, Anna; Re, Maria Carla; Varani, Stefania
Highlights: Most leishmanial infections remain asymptomatic in immunocompetent individuals. Leishmaniasis is endemic in the province of Bologna, northeastern Italy. We tested 240 blood donors in the Bologna province to detect asymptomatic Leishmania infection. Highly sensitive serological test, ie Western Blot, was employed in combination with a real time PCR assay. The prevalence of asymptomatic Leishmania infection in the Bologna province was 12.5%. Abstract: Objectives: Human leishmaniasis can be severe and fatal, yet in the Mediterranean region only a small percentage of infections progress to clinical disease. We evaluated the percentage of asymptomatic Leishmania infection in the Bologna province, northeastern Italy. Methods: We examined the presence of specific antibodies by Western Blot (WB) and parasitic DNA by real time PCR in peripheral blood of 240 blood donors residing in the Bologna province. Results: Anti- Leishmania IgG were detected by WB in 27 subjects (11.2%, 95% CI 7%-15%), while Leishmania kinetoplast DNA was detected in peripheral blood specimens of 4 out of 240 donors (1.7%, 95% CI 0.2%-3.2%). Overall, the prevalence of Leishmania infection in the blood donor cohort was 12.5%, thus indicating an elevated cumulative exposure to the Leishmania parasite in the examined municipality. Conclusions: Our results suggest that a surveillance system for monitoring Leishmania infection in blood donors and/or strategies of protozoan inactivation in whole blood should be taken into consideration in areas with circulation of the Leishmania parasite.